Features of the cytokine profile and the effectiveness of radical treatment of focal infection in patients with psoriasis - Aleksandr V. Patrushev; Alexey V. Samtsov; Alexey V. Soukharev (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Background. Focal infection (FI) are important trigger factors for the development of psoriasis, which means they can aggravate the course of dermatosis, including due to an increase in certain pro-inflammatory cytokines in the blood. Aim. To study the cytokine profile of patients with psoriasis in the progressive period of the disease, as well as to assess the effect radical treatment of focal infection on the course of dermatosis. Material and methods. Prospective comparative non-randomized study included 52 patients with psoriasis vulgaris, aged 18 to 65 years, who signed a informed consent. The first group consisted of patients who underwent radical treatment FI (16 people), the second those who did not treat FI (16 people), and the third group consisted of patients in whom FI was not detected (20 people). Cytokine concentrations were measured in the progressive stage of the disease in 52 patients with psoriasis and 20 individuals in the control group (healthy individuals).The spectrum of detected cytokines included: IL-1, IL-2, IL-4, IL-6, IL-8, IL-10, IL-17A, as well as INF- and INF-. For the detection of all cytokines, except for IL-17A, reagents from Vector-Best, Russia were used. The Human ELISA MAX Deluxe Set (BioLegend, USA) was used to determine the concentration of IL-17A. During the main course of treatment (0, 2 and 4 weeks), as well as the follow-up of patients (12, 24 and 52 weeks), the severity of psoriasis was assessed with the calculation of the PASI index. At the end of the study (week 52), the number of relapses and the total duration of remission were recorded. Results. The level of IL-8 was increased in 90,6% of psoriasis patients with FI. In this case, significant differences were obtained in comparison with the group of patients with psoriasis without diagnosed FI and with the control group, in which an increase in the concentration of IL-8 was noted, respectively, in 65% and 30% of cases. A moderate positive correlation was found between the IL-8 level and the PASI index (rs = 0,48; p = 3,6 104). The levels of INF- and IL-6 in psoriasis patients with FI were increased, respectively, in 15,6% and 21,9% of cases and significantly differed from the group of practically healthy individuals (p 0,05), differences from the group of patients with psoriasis without FI was not identified. The concentration of TNF- did not differ in all three groups. The level of IL-17A was significantly increased in comparison with practically healthy individuals both in the group of psoriasis patients with FI and in the group of patients without FI (Me = 3,3 and 4,3 pg/ml versus 0,2 pg/ml). The concentrations of five interleukin cytokines, namely IL-1, IL-2, IL-4, IL-10 and INF-, did not exceed the upper limit of the reference range in all patients of the experimental (patients with psoriasis) and control groups. Evaluation of the PASI index during the observation of patients in the first and second groups showed significantly lower values of this indicator for weeks 24 and 52 in the first group (0,2 vs. 7,0; p = 0,02 and 0,1 vs. 7,2; p = 0,002). The relative risk of disease recurrence in the absence of radical treatment for FI was 2,6 (CI 1,1 to 5,2). Conclusion. Data were obtained showing the role of IL-8 and focal infection, with the presence of which its increased production is associated, in the worsening of the course of psoriasis with the frequent development of relapses. Important preventive measures leading to a decrease in the number of relapses of psoriasis are timely diagnosis and radical treatment of focal infection.